The Diagnostic Value of Ultrasound in Medullary Thyroid Carcinoma: A Comparison With Computed Tomography. (5th February 2020) - Wang, Liang; Kou, Hongju; Chen, Wei; Lu, Mingdong; Zhou, Lingling; Zou, Chunpeng
Purpose: To explore the clinical value of ultrasound in the diagnosis of medullary thyroid carcinoma by comparing with enhanced computed tomography. Methods: This retrospective study was performed on 62 patients with pathologically confirmed medullary thyroid carcinoma. All patients underwent ultrasound and enhanced computed tomography examinations before surgery. The findings of the pathologic examination of resected specimens were considered as gold standard and were compared with the results of these 2 methods. Results: There were 73 medullary thyroid carcinoma lesions and 29 benign lesions in 62 patients. In all, 55 of 73 medullary thyroid carcinoma lesions and 27 of 29 benign lesions were correctly diagnosed by ultrasound; and 45 of 73 medullary thyroid carcinoma lesions and 24 of 29 benign lesions were correctly diagnosed by enhanced computed tomography. The accuracy of ultrasound and enhanced computed tomography was 80.4% and 67.6%, respectively. There was significant difference between 2 methods ( P < .05). Conclusions: Ultrasound can be used to observe the location, number, size, shape, border, internal echo, calcification, and blood flow of the lesion. It is a convenient, inexpensive, and nonradiative method with higher accuracy than enhanced computed tomography.